1998
DOI: 10.1111/j.1600-0528.1998.tb02022.x
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence of toothwear in users of Ecstasy (3,4 MethyleneDioxyMethAmphetamine)

Abstract: The severity of toothwear and the number of teeth affected were greater in Ecstasy users than in a group of non-users. The occlusal surfaces were more commonly affected than the incisal, which may indicate jaw clenching rather than grinding as a feature of Ecstasy-induced muscle hyperactivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
4

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 13 publications
2
49
0
4
Order By: Relevance
“…Type of drug abuse is associated with the oral health sensations produced, as evident in the difference in recalled oral health sensations among 'ecstasy' and 'non-ecstasy' abusers. or clenching their teeth together' after taking drugs compared to 28% (14) of those who never abused 'ecstasy', P < 0.001. Also, 70% (48) of those who abused 'ecstasy' claimed they felt 'pain or tenderness in their jaw muscle or jaw joints' compared to 36% (18) non 'ecstasy' abusers, P < 0.001.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Type of drug abuse is associated with the oral health sensations produced, as evident in the difference in recalled oral health sensations among 'ecstasy' and 'non-ecstasy' abusers. or clenching their teeth together' after taking drugs compared to 28% (14) of those who never abused 'ecstasy', P < 0.001. Also, 70% (48) of those who abused 'ecstasy' claimed they felt 'pain or tenderness in their jaw muscle or jaw joints' compared to 36% (18) non 'ecstasy' abusers, P < 0.001.…”
Section: Resultsmentioning
confidence: 99%
“…Anecdotal concerns have been raised about the effects of 'ecstasy' abuse on tempromandibular joint dysfunction. 14,17,[26][27] …”
Section: Abuse Of 'Ecstasy' and Oral Health Sensationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Milosevic et al [10] reported that tooth-wear through the enamel into the underlying dentine occurred in 18 (60%) ecstasy users, xerostomia occurred in 93% of ecstasy users and 89% reported that they clenched or ground their teeth after taking the drug. Furthermore, Milosevic et al [10] concluded that the occlusal surfaces were more commonly affected than the incisal, which may indicate jaw clenching rather than grinding as a result of ecstasy-separate induced muscle hyperactivity.…”
Section: Discussionmentioning
confidence: 99%